2012
DOI: 10.4187/respcare.01681
|View full text |Cite
|
Sign up to set email alerts
|

Heated and Humidified High-Flow Oxygen Therapy Reduces Discomfort During Hypoxemic Respiratory Failure

Abstract: Upper airway caliber was not significantly modified by HHFO₂, compared to standard oxygen therapy, but HHFO₂ significantly reduced discomfort in critically ill patients with respiratory failure. The system is usually preferred over standard oxygen therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 23 publications
2
93
0
3
Order By: Relevance
“…[21][22][23] In addition, all of these mechanisms also explain why HFNC improved gas exchange and subject comfort. The advantage of HFNC in terms of improving dyspnea, subject comfort, and oxygenation has also been noted in other subject populations, such as post-cardiac surgery 8 and postendotracheal extubation subjects, 7,9 and during fiberoptic bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] In addition, all of these mechanisms also explain why HFNC improved gas exchange and subject comfort. The advantage of HFNC in terms of improving dyspnea, subject comfort, and oxygenation has also been noted in other subject populations, such as post-cardiac surgery 8 and postendotracheal extubation subjects, 7,9 and during fiberoptic bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…This excellent tolerance, systematically reported with HFNC during acute hypoxemic failure, 4,15,16 is attributable, at least in part, to the heat and humidity supplied by the device. 35 We reported a case of prolonged HFNC use for over 30 d. 36 …”
Section: Comfortmentioning
confidence: 98%
“…Standard oxygen through face mask provides non-humidified or under-humidified cold gas that dries the upper airway and leads to reduced patient comfort, even when a bubble humidifier is used (30). Most studies have reported better comfort and dyspnea feeling with HFNC than with standard oxygen through a mask or NIV (10,17,(31)(32)(33) with subsequently improved compliance (34).…”
Section: Comfort and Humidificationmentioning
confidence: 99%